Evaluasi Waste Waktu Tunggu dan Produk Cacat Pembuatan Produk Furniture dalam Upaya Peningkatan Produksi Pada UD. Sinar Indah - Firmansyah, Aditya Nur; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Productivity is one of the key factors in enhancing industrial competitiveness, particularly in the furniture manufacturing sector. This study aims to analyze the types and sources of waste occurring in the production process at UD. Sinar Indah and to formulate improvement strategies to increase productivity. The research applies the lean manufacturing approach by identifying the seven types of waste commonly found in production activities. Data were collected through direct observation on the shop floor, interviews with employees, and process time recording. The findings indicate that the most dominant wastes are waiting time and inefficient movements, which significantly affect productivity levels. Recommended improvements include workplace layout rearrangement, standardization of procedures, and enhancement of operator skills. By implementing these improvements, UD. Sinar Indah has the potential to increase productivity while reducing production costs.